Analytical assessment of Ain Skhouna PV plant performance connected to the grid under a semi-arid climate in Algeria - Mohamed El hassen Jed; Razika Ihaddadene; Nabila Ihaddadene; Amaury De Souza (université de msila, 2021)
Algeria currently has a number of 24 functional photovoltaic power plants on its national territory, which are poorly investigated. This study focuses on the performance analysis of one of these existing solar power plants. It is located in Ain Skhouna, situated in Saida province, and has a capacity of 30 MWp (polycrystalline solar cell technology). This study was carried out according to the standardized norms IEC 61,724 (IEC) using one year (2018) of data. A linear relationship between the monthly module and ambient temperatures was evaluated (R2 = 0.994). The monthly total loss increases linearly with the increase in monthly ambient temperature and solar irradiation (R2 = 0.98). The system efficiency, PV efficiency, and performance ratio are affected by ambient temperature. The average monthly PV, system, inverter efficiencies, and PR were 13.78%, 13.29%, 96.68%, and 85.52, respectively. These results indicate that this PV power plant remains in very good working condition after two years of service. The effect of climate on PV plant performance was investigated in Algeria by comparing two climates: a semi arid and a hyper-arid. The results indicate that the semi-arid climate is more favorable than the desert climate for PV power plants for producing electricity and that ambient temperature is a more essential parameter than solar irradiation.
Keywords: Grid connected Photovoltaic system Standardized performance analysis Performance ratio System efficiency Semi-arid climate